EVALUATION OF FETOMATERNAL OUTCOMES USING AMNIOTIC FLUID INDEX AND SINGLE DEEPEST VERTICAL POCKET FOR AMNIOTIC FLUID VOLUME ASSESSMENT - Haroon, Mariyam; Choudry, Abeera; Ahmed, Madiha; Gul, Mahwish; Altaf, Anam (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare fetomaternal outcomes using amniotic fluid index and single deep vertical pocket for estimating amniotic fluid volume among pregnant women. Study Design: Comparative prospective study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital, Rawalpindi, from Aug 2019 to Feb 2020. Methodology: Sample of 110 pregnant women was calculated with WHO calculator. We used non probability consecutive sampling as effective sampling technique. Research approval and patient consent were taken before initiation of study. Patients were randomly divided into two groups; group A underwent amniotic fluid index measurement while group B underwent single deep vertical pocket measurement. Feto maternal outcomes were measured in both groups. Results: Total 110 pregnant women were included in our study (55 women in each group). Mean age of women was 26.9 ± 4.6 SD. In Amniotic fluid index group, preeclampsia 14 (12.7%) vs 5 (4.5%) respectively, p=0.04, rupture of membrane 12 (10.9%) vs 4 (3.6%) respectively, p=0.05 was significantly higher as compared to single deep vertical pocket group. Patients with oligohydroamnios were significantly higher in amniotic fluid index group as compared to single deep vertical pocket 15 (13.6%) vs 3 (2.7%), respectively, p=0.04. Conclusion: Amniotic fluid volume assessment could be done with both amniotic fluid index and single deep vertical pocket method. Single deep vertical pocket is safe, effective and better diagnostic choice for amniotic fluid assessment as it is associated with avoidance of unnecessary interventions without affecting peripartum outcomes.